Local Climate Change Adaptation under the Lenses of Public Health: A Case Study from Porto, Portugal - José Pedro Silva; Gloria Macassa; Henrique Barros; Ana Isabel Ribeiro (Portuguese Journal of Public Health)
Introduction: Climate change is a pressing public health issue. Urban populations, especially in coastal areas, are highly vulnerable. As climate change progresses, local adaptation becomes increasingly important. We present a case study about the inclusion of public health concerns in local climate change adaptation in Porto (Portugal). Methods: We analysed two local adaptation plans using qualitative content analysis and conducted semi-structured interviews with a purposeful sample of 6 key stakeholders with different profiles. We did a qualitative content analysis of the respective transcripts. Results: Porto is undergoing health-relevant consequences of climate change, which are expected to worsen further in the future. Porto’s geographical and demographic characteristics and urban environment make its population highly vulnerable to climate change-related health risks. Public health is recognized as a central element in local adaptation efforts. Drivers for integrating health concerns include growing climate change awareness, a sense of urgency, social capital, institutional networks, access to resources, and political commitment. Nevertheless, challenges like data limitations, resource constraints, climate knowledge gaps, communication issues, and political cycles hinder both local adaptation and the integration of health considerations. Discussion/Conclusion: In Porto, health seems both a powerful mobilizing issue and a central topic concerning local adaptation. However, the complex and long-term nature of climate change and the associated uncertainty hinder adaptation efforts. High-quality data about both the local climate and population health are thus essential. The transversal nature of risk is recognized and multi-sectorial approaches, public participation, mainstreaming, and policy integration are necessary to prevent imbalances. Local adaptation efforts, including health-related efforts, are shaped by the international (belonging to the European Union), national, and local contexts. Successful local adaptation and inclusion of health aspects require mainstreaming and policy integration across different areas and involvement of multiple stakeholders, including the population, in order to maximize resources and avoid undesired trade-offs.